PENTINGNYA PROFESI AKUNTAN DALAM PENGEMBANGAN LAPORAN KEUANGAN DESA - Rindiyani Abdullah; Mardiana Mardiana; Firawati A. Jabu; Wiwin Salim (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2021)
Under Law No. 6 of 2014 which states that the village will receive funding of 1.4 Billion for rural development. Where the funds will be paid out in stages that began the first stage in April 2015. So by the constraints of the current government has not issued regulations governing the financial processing village government also states to immediately implement the process of preparation of financial statements in the village using generally accepted accounting standards, For that, is necessary to enter the village accountant for the success of the program of the government. Whereas in reality, many accounting scholars today who does not have the necessary skills to education majors. So, should the formal education system that is associated with this department more matured more. Thus, it can help to better understand the bureaucracy village again on the financial statements. But, in fact, many villagers are still not open to the arrangement report for village development standards